The pattern of coronavirus cases in South Africa compared with the United States of America and South Korea - Mafugu, Tafirenyika; Sanderson, Abel (Women's Health and Action Research Centre, 2021)
The coronavirus pandemic has spread worldwide, causing massive deaths of people in different countries. The study sought to find successes and failures in preventing the spread of the disease. This study results would assist states in identifying practical measures that can be used to avoid the spread of the pandemic. The cross-sectional study used a comparative analysis method. The study employed cross country comparison to conclude the effectiveness of the various measures implemented by different countries. Seven key phrases were searched, and the results were considered for analysis and presentation. The data were analyzed using the paired sample t-test and spearman's correlation coefficient. The USA and South Africa are on the exponential growth phase for the total number of infections per day. At the same time, South Korea and Taiwan were able to contain the virus. Western Cape is the epicenter of coronavirus cases in South Africa. The extensive production of face masks, quarantine measures, banning overseas travel, physical distancing, monitoring self-isolating individuals may help to contain the virus. In South Africa, banning the interprovincial movement may keep the spread to a minimum. Rapid implementation of preventive measures in the early stages is vital in preventing the spread of the pandemic.